IMPLEMENTASI KURIKULUM 2013 DENGAN PENDEKATAN SAINTIFIK (SCIENTIFIC APPROACH) PADA MATA PELAJARAN BIOLOGI - Miska Khairani Siregar; Amrizal Amrizal (Jurnal Pelita Pendidikan, 2018)
The aims of this research is to determine the implementation 2013 curriculum based scientific approach on biology, to obtain data on the results of the 2013 curriculum achievement in learning planning aspects, implementation of learning and learning assessment. This research design using descriptive research with check list observation method and is conducted in 3 meetings. The Sample of research is 2 biology teachers in class x who applied 2013 curriculum. Data collection with observation sheets and interview guidelines which as where for as many as 30 questions for learning planning, 38 questions for implementation of learning, and 12 questions for learning assessment. Results was indicated the average of learning planning was 85.00% cathegorized as done, implementation of learning was 79.30% cathegorized as enough, and learning assessment was 79.16% cathegorized as enough. Based on the results, implementation 2013 curriculum based scientific approach in SMA Negeri 3 Binjai is had not maximal get and need to be replaced. Keywords: 2013 curriculum, scientific approach, planning, implementation, assessmen